Pengaruh Biochar Sekam Padi dan Pupuk Kandang Kotoran Ayam Terhadap Kesuburan Ultisol dan Hasil Kacang Tanah (Arachis hypogea L.) - Bilhuda, Abi Mayu; Riduan, Ahmad; Junedi, Heri (Jurnal Media Pertanian, 2024)
Peanuts are a legume commodity that ranks second after soybeans and have the potential to be a strategic commodity because demand is quite large every year, both for food, feed and industry. Ultisol soil is soil that is less fertile and unproductive for most plants. Organic matter can improve soil conditions and provide nutrients for plants. Biochar is a soil amendment material made from various crop residues that has potential and has a high C/N ratio or is difficult to decompose. The aim of this research is to determine the effect of rice husk biochar combined with chicken manure on improving the fertility of Ultisol, on peanut yield. , and determine the best dose of rice husk biochar combined with chicken manure for peanut yield on Ultisol soil. The research was carried out at the experimental field of the Agricultural Training Center Jl. Jambi â€“ Palembang, KM 16 Pondok Meja Village, Mestong District, Muaro Jambi Regency, from May to August 2022. Research usingRandomized Block Design (RAK), with 9 treatments, namely chicken manure (P0B0 = Without biochar and chicken manure, P1B0 = 10 tons ha-1 chicken manure, P2B0 = 15 tons ha-1 chicken manure manure, P0B1 = 5 ton ha-1 biochar, P0B2 = 10 tons ha-1 biochar, P1B1 = 10 tons ha-1 chicken manure + 5 tons ha-1 biochar, P1B2 = 10 tons ha-1 chicken manure + 10 tons ha- 1 biochar, P2B1 = 15 tons ha-1 chicken manure + 5 tons ha-1 biochar, P2B2 = 15 tons ha-1 chicken manure + 10 tons ha-1 biochar) and 3 groups as replications, so that in the research There are 27 experimental plots. The observation variables in this research were plant height, number of leaves per plant, flowering age, number of pods per plant, pod weight per plant, dry pod weight per plot, weight of 100 seeds, plant yield per hectare, and plant P and K nutrient uptake. To determine the effect of treatment, a 5% level of analysis of variance (ANOVA) was carried out. The results of the research show that the application of rice husk biochar combined with chicken manure affects the fertility of ultisol, namely by increasing the soil pH to close to neutral, the elements of total N, total P, total K and available P so that it influences the variables of plant height, number of leaves, number of pods per plants, plant P and K uptake, dry weight of pods per plant, dry weight of pods per plot, weight of 100 seeds, and plant yield per hectare.Â Keywords: Peanuts, Ultisol, Biochar, Chicken Manure.